The Influence of Principal's Leadership and School's Climate on The Work Productivity of Vocational Pharmacy Teachers in Indonesia - Mediarita Agustina; Muhammad Kristiawan; Tobari Tobari (Universitas Bengkulu, 2021)
This study determined the effect of school principal leadership and school climate on the work productivity of SMK Pharmacy teachers in Palembang. Data in this study were collected through questionnaire distribution to respondents. The results of filling out the questionnaire were analyzed by multiple regression analysis through t test, F test, and the coefficient of determination test. The population in this study were all teachers who teach at the Pharmacy Vocational School in Palembang from 8 schools totaling 151 people. The sample in this study was based on calculations using the Slovin formula. So that the number of samples obtained in this study were 110 teachers. The results of this study indicate (1) there is a significant influence of school principal leadership on teacher work productivity; (2) there is a significant influence of school climate on teacher work productivity; (3) there is a significant influence of school principals leadership and school climate together on teacher work productivity. This paper contributes to educational principal to improve leadership and climate whether they would have very good teacher’s work productivity.